Effect of Aqueous Extract from Phaseolus vulgaris Pods on Lipid Peroxidation and Antioxidant Enzymes Activity in the Liver and Kidney of Diabetic Rats - Mariana Yuriivna Kyznetsova, Olha Mycholaivna Makieieva, Dariia Oleksandrivna Lavrovska, Maria Oleksandrivna Tymoshenko, Daryna Pavlivna Sheverova, Tetiana Ivanivna Halenova, Oleksiy Mycholayovych Savchuk, Lyudmila Ivanivna Ostapchenko (Journal of Applied Pharmaceutical Science, 2015)
The social significance of diabetes mellitus lies in the fact that in addition to significant prevalence, this disease is associated with many complications. To facilitate the course of diabetes and its complications medicinal plants are widely used in traditional medicine. One of such plants is kidney bean (Phaseolus vulgaris). This plant is used in traditional medicine, especially for the secondary complications of diabetes. Since complications of diabetes are often associated with increased oxidative stress, the study of antioxidant properties of P. vulgaris is important to clarify the mechanism of its therapeutic effect. Present investigation shows that long-term oral administration of aqueous P. vulgaris pods extract in dose of 200mg/kg b.w. besides its pronounced hypoglycemic action also has a positive influence on the liver and kidney function markers in STZ-treated diabetic rats. The extract also inhibits free radical production and lipid peroxidation and activates antioxidant enzymes in liver and kidneys of rats with STZ-induced diabetes. Thus, our data reveal antioxidant properties of aqueous P. vulgaris pods extract that might have beneficial effect in treatment of diabetes.
Keywords: Oxidative stress, kidney bean, Phaseolus vulgaris, streptozotocin-induced diabetes.